Discovering computers fundamentals 2011 : living in a digital world - Shelly, Gary B.; Vermaat, Misty E. (Boston, Massachusetts : Course Technology Cengage Learning, 2011)
Suitable for use in a short course on computer concepts or in application software courses, this title helps students gain an understanding of the various trends in technology and computer concepts as they are applied to digital world.
1. Introduction to computers -- A world of computers -- What is a computer? -- The components of a computer -- Advantages and disadvantages of using computers -- Networks and the Internet -- Computer software -- Categories of computers -- Personal computers -- Mobile computers and mobile devices -- Game consoles -- Servers -- Mainframes -- Supercomputers -- Embedded computers -- Examples of computer usage -- Computer applications in society -- Chapter summary -- Companies on the cutting edge -- Technology trailblazers -- Student assignments -- Chapter review -- Key terms -- Checkpoint -- Problem solving -- Learn how to -- Learn it online -- Web research -- Special feature : timeline 2011 -- -- 2. The Internet and World Wide Web -- The Internet -- The World Wide Web -- Other Internet services -- Netiquette -- Chapter summary -- Companies on the cutting edge -- Technology trailblazers -- Student assignments -- Chapter review -- Key terms -- Checkpoint -- Problem solving -- Learn how to -- Learn it online -- Web research -- Special feature : making use of the Web -- 3. Application software -- Business software -- Graphics and multimedia software -- Software for home, personal, and educational use -- Web applications -- Application software for communications -- Learning tools for application software -- Chapter summary -- Companies on the cutting edge -- Technology trailblazers -- Student assignments -- Chapter review -- Key terms -- Checkpoint -- Problem solving -- Learn how to -- Learn it online -- Web research -- Special feature : digital communications. 4. The components of the system unit -- The system unit -- Processor -- Data representation -- Memory -- Expansion slots and adapter cards -- Ports and connectors -- Buses -- Bays -- Power supply -- Putting it all together -- Keeping your computer or mobile device clean -- Chapter summary -- Companies on the cutting edge -- Technology trailblazers -- Student assignments -- Chapter review -- Key terms -- Checkpoint -- Problem solving -- Learn how to -- Learn it online -- Web research -- 5. Input and output -- What is input? -- Keyboard and pointing devices -- Touch screens and touch-sensitive pads -- Pen input -- Other types of input -- What is output? -- Display devices -- Printers -- Other output devices -- Putting it all together -- Input and output devices for physically challenged users -- Chapter summary -- Companies on the cutting edge -- Technology trailblazers -- Student assignments -- Chapter review -- Key terms -- Checkpoint -- Problem solving -- Learn how to -- Learn it online -- Web research -- Special feature : digital video technology -- 6. Storage -- Hard disks -- Flash memory storage -- Cloud storage -- Optical discs -- Other types of storage -- Putting it all together -- Chapter summary -- Companies on the cutting edge -- Technology trailblazers -- Student assignments -- Chapter review -- Key terms -- Checkpoint -- Problem solving -- Learn how to -- Learn it online -- Web research. 7. Operating systems and utility programs -- System software -- Operating systems -- Operating system functions -- Types of operating systems -- Stand-alone operating systems -- Server operating systems -- Embedded operating systems -- Utility programs -- Chapter summary -- Companies on the cutting edge -- Technology trailblazers -- Student assignments -- Chapter review -- Key terms -- Checkpoint -- Problem solving -- Learn how to -- Learn it online -- Web research -- Special feature : buyer's guide 2011 : how to purchase computers and mobile devices -- 8. Communications and networks -- Communications -- Uses of computer communications -- Communications software -- Communications over the telephone network -- Communications devices -- Home networks -- Communications channel -- Physical transmission media -- Wireless transmission media -- Chapter summary -- Companies on the cutting edge -- Technology trailblazers -- Student assignments -- Chapter review -- Key terms -- Checkpoint -- Problem solving -- Learn how to -- Learn it online -- Web research -- 9. Database management -- Databases, data, and information -- The hierarchy of data -- Maintaining data -- File processing versus databases -- Database management systems -- Relational, object-oriented, and multidimensional databases -- Web databases -- Database administration -- Chapter summary -- Companies on the cutting edge -- Technology trailblazers -- Student assignments -- Chapter review -- Key terms -- Checkpoint -- Problem solving -- Learn how to -- Learn it online -- Web research. 10. Computer security, ethics, and privacy -- Computer security risks -- Internet and network attacks -- Unauthorized access and use -- Hardware theft and vandalism -- Software theft -- Information theft -- System failure -- Backing up--the ultimate safeguard -- Wireless security -- Health concerns of computer use -- Ethics and society -- Information privacy -- Chapter summary -- Companies on the cutting edge -- Technology trailblazers -- Student assignments -- Chapter review -- Key terms -- Checkpoint -- Problem solving -- Learn how to -- Learn it online -- Web research -- 11. Information system development and programming languages -- System development -- Programming languages and program development tools -- Program development -- Chapter summary -- Companies on the cutting edge -- Technology trailblazers -- Student assignments -- Chapter review -- Key terms -- Checkpoint -- Problem solving -- Learn how to -- Learn it online -- Web research -- 12. Enterprise computing -- What is enterprise computing? -- Information systems in the enterprise -- Enterprise-wide technologies and methodologies -- Virtualization and cloud computing -- E-commerce -- Enterprise hardware -- High availability scalability, and interoperability -- Backup procedures -- Chapter summary -- Companies on the cutting edge -- Technology trailblazers -- Student assignments -- Chapter review -- Key terms -- Checkpoint -- Problem solving -- Learn how to -- Learn it online -- Web research -- Special feature : living digitally -- Appendix A. Quiz yourself answers -- Glossary/Index -- Photo credits.
Includes index.
Keywords: COMPUTERS